A Study of the Associated Risk Factors for Early Failure and the Effect of Photofunctionalisation in Full-Arch Immediate Loading Treatment Based on the All-on-Four Concept - Takashi Uesugi; Yoshiaki Shimoo; Motohiro Munakata; Yu Kataoka; Daisuke Sato; Kikue Yamaguchi; Minoru Sanda; Michiya Fujimaki; Kazuhisa Nakayama; Tae Watanabe; Paulo Malo (Bioengineering, 2024)
Early implant failure occurring within 1 year after implantation has been attributed to various factors. Particularly, early failure can lead to challenges in maintaining a full-arch prosthetic device, necessitating prompt intervention, including reoperation. This study aimed to retrospectively examine implant- and patient-related factors and the effects of photofunctionalisation associated with early failure in patients who underwent treatment using the all-on-four concept in both the maxilla and mandible. We conducted this retrospective study comprising 561 patients with 2364 implants who underwent implant-supported immediate loading with fixed full-arch rehabilitation using the all-on-four concept. We aimed to assess the survival rate within 1 year after implantation and determine the risk factors influencing early failure. The 1-year survival rates after implantation were 97.1% (patient level) and 98.9% (implant level) for the maxilla and 98.5% (patient level) and 99.6% (implant level) for the mandible. There was a significant difference in the implant-level survival rates between the maxilla and mandible, with a lower rate in the maxilla (p = 0.043). The risk factors associated with early implant failure according to the all-on-four concept included the maxilla (implant level) and smoking (patient level). We could not find a significant effect of photofunctionalisation on early failure (p = 0.25) following this treatment protocol.